Boys don't cry [videorecording (DVD)] - Peirce, Kimberly; Swank, Hilary; Sevigny, Chloë; Sarsgaard, Peter; Sexton, Brendan, 1980- (Twentieth Century Fox Home Entertainment, 2000)
A transgendered youth starts living as a man, and assumes the name Brandon Teena. He moves to a tiny Nebraska town and begins making new friends under his new identity. All goes well until his new friends discover his secret. Based on a true story about hope, fear, and the courage it takes to be yourself.